2019
DOI: 10.1080/1528008x.2019.1616039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of Environmental Education in Manesht and Ghelarang Geotourism Destination, Iran

Abstract: The aim of this study is to investigate the land ethics of tourists regarding the geotourism resources in the Protected Area of Manesht and Ghelarang, Ilam Province, Iran. The theoretical framework of the research is based on environmental knowledge, environmental behavior, normative pressures, facilities, multiple incentive models, ability, opportunity and environmental ethics model. Approximate number of tourists visiting (local tourist) the protected area in the specified time range (spring 2017) was 3,000.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…Por su parte, Mokhtari et al (2019) resaltaron en su investigación sobre geoturismo, la importancia de los lugares protegidos en el mantenimiento de la biodiversidad y los sistemas naturales, y concluyen que es necesario considerar las facilidades de infraestructura que generen la oportunidad de realizar comportamientos adecuados como mapas de la zona, y facilidades higiénicas como recipientes para arrojar residuos; tal como lo indican D'Souza et al ( 2019) se debe buscar generar una relación de simbiosis entre turistas y la comunidad residente. Los beneficios no son solo económicos, también aporta a la salud en general, debido a una adecuada calidad del medio ambiente.…”
Section: Resultsunclassified
“…Por su parte, Mokhtari et al (2019) resaltaron en su investigación sobre geoturismo, la importancia de los lugares protegidos en el mantenimiento de la biodiversidad y los sistemas naturales, y concluyen que es necesario considerar las facilidades de infraestructura que generen la oportunidad de realizar comportamientos adecuados como mapas de la zona, y facilidades higiénicas como recipientes para arrojar residuos; tal como lo indican D'Souza et al ( 2019) se debe buscar generar una relación de simbiosis entre turistas y la comunidad residente. Los beneficios no son solo económicos, también aporta a la salud en general, debido a una adecuada calidad del medio ambiente.…”
Section: Resultsunclassified
“…Other researchers [61,62] conducted studies on the role of environmental education in geotourism destinations and the significance of urban geomorphological heritage for urban geotourism development. The first study indicated that the lowest score was related to environmental knowledge and facilities.…”
Section: Research Backgroundmentioning
confidence: 99%
“…This condition was in accordance with the results of research conducted by Norrish et al (2014) on stakeholder perceptions of geotourism development in Perth Australia. The education aspect was a concern of stakeholders because geotourism products were rich in educational content, especially education about natural phenomena and geological/geological phenomena (Farsani et al, 2018;Mokhtari et al, 2019;Norrish et al, 2014;Walliss & Kok, 2014). The education aspect of travel should be a serious concern because the low interpretation and minimal number of tour guides can actually increase the negative impact on geotourism resources and the environment such as vandalism (doodles/graffiti), littering and other negative behaviors.…”
Section: Perceptions Of Geotourism Developmentmentioning
confidence: 99%
“…Earthquakes, tsunamis, ground movements, volcanic eruptions, liquefaction and drought are examples of many types of geological disasters which in the last two decades have increased their frequency of occurrence. With geotourism activities that are full of educational activities, it is hoped that tourists and the wider community will have additional knowledge about how to adapt and mitigate against these natural disasters (Newsome & Johnson, 2013;Farsani et al, 2018;Mokhtari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%